Problems with the Institutional Form of the Implementing Agency of Social Security in Indonesia - Rohanawati, Ayunita Nur; Yuniza, Mailinda Eka (Fakultas Hukum Universitas Islam Indonesia, 2024)
The administration of social security in Indonesia is entrusted to two newly formed institutions as mandated by Law Number 40 of 2004 concerning National Social Security System, namely BPJS for Health and BPJS for Employment. The basis for the operation of these two institutions is Law Number 24 of 2011 concerning the Implementing Agency of Social Security. These two bodies are public legal entities that were formed from the transition to the previous form of a limited liability company, namely PT Jamsostek (persero) and PT Askes (persero). The new form of the social security implementing agency as mentioned creates problems that need to find solutions to various problems that occur. Therefore, the purpose of this research is to find out what are the problems with the institutional forms of the Implementing Agency of Social Security in Indonesia. The method used in this research is to use juridical, namely by examining the legal materials, both primary legal materials, secondary legal materials, and tertiary legal materials used. The approach used is a statutory approach and a comparative approach. The research results show that there are problems that arise in the institutions administering social security in Indonesia. These problems are related to the governance of the agency, from the formation process, changes in characteristics from a limited liability company to a public legal entity, the failure to merge social security administering bodies as contained in Law Number 24 of 2011 concerning Social Security Administering Bodies and related to employment aspects in the social security administration body.Keywords: Agency of Social Security; Institutional Form; National Social Security System. AbstrakPenyelenggaraan jaminan sosial di Indonesia dipercayakan kepada dua lembaga yang baru dibentuk sebagaimana diamanatkan Undang-Undang Nomor 40 Tahun 2004 tentang Sistem Jaminan Sosial Nasional, yaitu BPJS Kesehatan dan BPJS Ketenagakerjaan. Landasan implementasi kedua lembaga tersebut yakni Undang-Undang Nomor 24 Tahun 2011 tentang Badan Penyelenggara Jaminan Sosial. Keduanya merupakan badan hukum publik yang terbentuk dari peralihan bentuk perseroan terbatas sebelumnya yaitu PT Jamsostek (persero) dan PT Askes (persero). Bentuk baru lembaga penyelenggara jaminan sosial sebagaimana disebutkan di atas menimbulkan permasalahan yang perlu dicari solusinya terhadap berbagai permasalahan yang terjadi. Oleh karena itu, penelitian ini bertujuan untuk mengetahui permasalahan yang terdapat pada bentuk kelembagaan Badan Pelaksana Jaminan Sosial di Indonesia. Metode yang digunakan dalam penelitian ini adalah metode yuridis, yaitu dengan meneliti bahan-bahan hukum, baik bahan hukum primer, bahan hukum sekunder, maupun bahan hukum tersier yang digunakan. Pendekatan yang digunakan adalah pendekatan perundang-undangan dan pendekatan komparatif. Hasil penelitian menunjukkan bahwa terdapat permasalahan yang muncul pada lembaga penyelenggara jaminan sosial di Indonesia. Permasalahan tersebut terkait dengan tata kelola lembaga, mulai dari proses pembentukan, perubahan ciri dari perseroan terbatas menjadi badan hukum publik, tidak adanya penggabungan badan penyelenggara jaminan sosial sebagaimana tertuang dalam Undang-Undang Nomor 24 Tahun 2011 tentang Badan Penyelenggaraan Jaminan Sosial dan terkait aspek ketenagakerjaan pada badan penyelenggara jaminan sosial.Kata Kunci: Badan Jaminan Sosial; Bentuk Kelembagaan; Sistem Jaminan Sosial Nasional.